In the Shadow of the French Revolution - Marija Kocić; Maja Vasiljević (Muzikološki Zbornik, 2019)
This paper was primarily based on correspondence of Marco Foscari IV, member of respectable patrician family who served from 1789 to 1792 as Captain Raspa of a small fortress in Istria. His correspondence with close friends discloses opportunities in Venice, as well as events related to its nightlife in which the theatre, along with opera, played the dominant role. Its focus is research on influence of French Revolution on Venetian theatre and opera. In search for micro level of analysis, authors put their focus on local perspective on French-Italian relations, and their influence on opera. Therefore, authors singled out one interesting event which sparked great public attention in Venice – debates and process of the construction of a new theatre in the San Fantino, sestiere de San Marco, theatre La Fenice. At the time of prohibition of the public and private gatherings, in early 1790s, in this paper authors analysed position of opera.